Experimenting with the Experimental Novel: José Donoso and Naturalism in Chile - Salvador Ayala Camarillo (Studies in 20th & 21st Century Literature, 2026)
As a prominent writer of the Latin American Boom, José Donoso presented himself as someone breaking radically with past literary forms in Chile, including literary naturalism. I argue that counter to this assertion, Donoso engages critically with the ideas of naturalism in what is considered his most innovative and least realistic novel, El obsceno pájaro de la noche (1970). His working with and later testing of the naturalist tradition parallels the work of an important Chilean predecessor, Augusto D’Halmar, whose own fiction plays with themes of lineage, blurred identities, and the irrational. Like D’Halmar’s Juana Lucero (1902), Donoso’s novel first engages in critiques of class and questions of heredity or determinism central to naturalism, only to challenge the genre’s rationality openly, as D’Halmar did in later works. Even in his most bewildering novel, Donoso deploys naturalist notions in two significant ways. The first is in his portrayal of two protagonists, Don Jerónimo Azcoitía and his assistant Humberto Peñaloza, and their obsession with genetic inheritance and acclaim. Donoso skewers both characters’ pretensions and, by extension, naturalism’s preoccupations with heredity. The second way the text grapples with naturalism is in Don Jerónimo Azcoitía’s efforts to create a microcosm of the world for his unnatural son. His attempt to create an experiment in which he controls all the variables falls apart, and in his portrayal of Azcoitía’s failed experiment, Donoso stages the limitations of Émile Zola’s roman expérimental model of narration. Ultimately, I demonstrate that taking into account the parallels between Donoso and D’Halmar reveals how Donoso offers less a clean break with naturalism than an intensification of an already existing tradition of reimagining and even queering the literary mode.
Keywords: Jose Donoso; Naturalism; Latin American Literature